Emily Wilde's Compendium of Lost Tales - Fawcett, Heather (London Orbit, 2025)
"Emily Wilde has spent her life studying faeries. A renowned dryadologist, she has documented hundreds of species of Folk in her Encyclopedia of Faeries. Now she is about to embark on her most dangerous academic project studying the inner workings of a faerie realm--as its queen. Along with her former academic rival--now fiancé--the dashing and mercurial Wendell Bambleby, Emily is immediately thrust into the deadly intrigues of Faerie as the two of them seize the throne of Wendell's long-lost kingdom, which Emily finds a beautiful nightmare filled with scholarly treasures. Emily has been obsessed with faerie stories her entire life, but at first she feels as ill-suited to Faerie as she did to the mortal world: How can an unassuming scholar such as herself pass for a queen? Yet there is little time to settle in, for Wendell's murderous stepmother has placed a deadly curse upon the land before vanishing without a trace. It will take all of Wendell's magic--and Emily's knowledge of stories--to unravel the mystery before they lose everything they hold dear." -- Provided by publisher
Keywords: Fairy tale -- Historical Fiction